2002
DOI: 10.1085/jgp.20028558
|View full text |Cite
|
Sign up to set email alerts
|

Channel Openings Are Necessary but not Sufficient for Use-dependent Block of Cardiac Na+ Channels by Flecainide

Abstract: Na+ channel blockers such as flecainide have found renewed usefulness in the diagnosis and treatment of two clinical syndromes arising from inherited mutations in SCN5A, the gene encoding the α subunit of the cardiac voltage–gated Na+ channel. The Brugada syndrome (BrS) and the LQT-3 variant of the Long QT syndrome are caused by disease-linked SCN5A mutations that act to change functional and pharmacological properties of the channel. Here we have explored a set of SCN5A mutations linked both to BrS and LQT-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(118 citation statements)
references
References 46 publications
(100 reference statements)
5
113
0
Order By: Relevance
“…A likely explanation is that AZD7009 binds to and inhibits the Nav1.5 channel in its inactivated state and that channel opening is required for the drug molecule to access the binding site. A similar block mechanism has been described for flecainide, which, like AZD7009, has a high pKa and is thus charged to a large extent at physiologic pH Liu et al, 2002).…”
Section: Characteristics Of Ion Channel Blockade By Azd7009mentioning
confidence: 53%
“…A likely explanation is that AZD7009 binds to and inhibits the Nav1.5 channel in its inactivated state and that channel opening is required for the drug molecule to access the binding site. A similar block mechanism has been described for flecainide, which, like AZD7009, has a high pKa and is thus charged to a large extent at physiologic pH Liu et al, 2002).…”
Section: Characteristics Of Ion Channel Blockade By Azd7009mentioning
confidence: 53%
“…Flecainide is a well‐characterized UDB of Na + channels (Liu et al ., 2002; Liu et al ., 2003). More recently, flecainide has emerged as an effective therapeutic agent for the treatment of CPVT both in combination with conventional β‐adrenoceptor blockade (van der Werf et al ., 2011; van der Werf et al ., 2012; Watanabe et al ., 2013) and as a monotherapy (Napolitano, 2016; Padfield et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Crucially, the consequence of flecainide interaction with the Na + channel differs from that with RyR2 channels in one very important way; although, access to the flecainide binding site in Na + channels requires the channel to be open, once bound, flecainide interacts preferentially with the inactivated closed conformation of the channel, prolonging this state, thereby limiting the channel's availability for further activation (Liu et al ., 2002). This limited egress of flecainide from the Na + channel facilitates the accumulation of block (or use‐dependence) with repetitive depolarizations of the cell (Liu et al ., 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, analysis of the experimental data suggested that the predominant pathway for lidocaine binding to the Na ϩ channel is provided by the preopen state of the channel (14,18). The assumption that ranolazine does not unbind from the inactivated state and is effectively trapped in the channel after accessing the binding site via the preopen/open state has previously been shown to be essential for the use-dependent block by flecainide (7).…”
Section: Methodsmentioning
confidence: 99%